МОНГОЛ ДАХЬ АРДЧИЛАЛ БА ТҮҮНИЙ ЧАНАР - Д.Ганбат (Politology, 2023)
For the quality of democracy, third-wave still faces a variety of problems. As the gap between democracy’s promise and reality widened, democratically elected government officials were corrupt, incapable of competing, government disregarded the voices of citizens, and a new vision of new democracies with weak voter confidence.